A conversation for now and later - Pilkington, Mark (2017)
Essay for the 'New Chapter' catalogue in conjunction with an exhibition of new photographs by HH Lateefa bint Maktoum, held at the Tashkeel Gallery Dubai, 18 January - 23 February 2017.